Factors Associated with Treatment Uptake Among Women with Acetic Acid/Lugol’s Iodine Positive Lesions of the Cervix in Cameroon - Manga SM; Shi L; Welty TK; DeMarco RF; Aronowitz T (International Journal of Women's Health, 2020)
Simon M Manga,1– 3 Ling Shi,1 Thomas K Welty,2 Rosanna F DeMarco,1 Teri Aronowitz1 1College of Nursing and Health Sciences, University of Massachusetts Boston, Boston, MA, USA; 2Cameroon Baptist Convention Health Services, Bamenda, Cameroon; 3Center for Women’s Reproductive Health, Department of Obstetrics and Gynecology, University of Alabama at Birmingham, Birmingham, AL, USACorrespondence: Simon M Manga Tel +237 671863768Email smanga@cbchealthservices.orgPurpose: Treatment of cervical precancer is the primary aim in secondary prevention of cervical cancer. The purpose of this study was to examine factors associated with treatment uptake among women with acetic acid/Lugol’s iodine positive lesions identified by digital cervicography (DC) in a cervical cancer prevention program in Cameroon.Patients and Methods: We conducted a cross-sectional survey of medical records from 2013 to 2018 of 755 women in Cameroon who screened positive with acetic acid/Lugol’s iodine in 2013.Results: Of the 755 women, 422 (55.9%) had treatment/biopsy on the same day or followed up later, but only 344 (45.6%) received treatment/biopsy and 333 (44.1%) were lost to follow-up. Overall, 180 (52.3%) of the 344 women were treated/biopsied the same day they were screened, and 164 (47.7%) were treated/biopsied after the initial visit. Women aged 30– 49 and HIV-positive women were significantly more likely to have received treatment or returned for treatment than women less than 30 and HIV-negative women. Of the 266 women who followed up at a later date, the lesions of 78 (29.3%) women regressed spontaneously without treatment. Women with low-grade lesions, HIV-negative women and women who had follow-up more than a year after the initial exam were significantly more likely to have spontaneous regression with regression rates of 30.6%, 32.1% and 62.2%, respectively (p< 0.001). Age was not a significant determinant of spontaneous regression (p=0.149).Conclusion: Efforts to increase treatment uptake are needed in this population, including adherence to same day “See and treat” policies.Keywords: cervical precancer, treatment uptake, cameroon, cryotherapy, thermal ablation, loop electrosurgical excision procedure